2021
DOI: 10.21037/atm-20-7225
|View full text |Cite
|
Sign up to set email alerts
|

Role of pre-operative frailty status in relation to outcome after carotid endarterectomy: a systematic review

Abstract: Carotid endarterectomy (CEA) is a surgical treatment option to prevent ischemic cerebrovascular accidents. Patients that present with pre-operative frailty might have an elevated risk for unfavorable outcomes after the CEA. A systematic search, using Medline, Embase, Web of Science and Cochrane Database, was performed for relevant literature on frailty in patients undergoing CEA. The study protocol was registered with PROSPERO (CRD42020190345). Eight articles were included. The pooled prevalence for pre-operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
3
1
Order By: Relevance
“…Recent researches showed that due to aging of body function, atherosclerosis, and other factors, patients undergoing carotid artery revascularization have a high degree of pre-operative frailty ( 38 , 39 ). Banning ( 40 ) found that the prevalence of pre-operative frailty of CEA is 23.9%, lower than the results of this study, which may be related to the inclusion of CAS patients and expanded sample size in this study.…”
Section: Discussioncontrasting
confidence: 73%
“…Recent researches showed that due to aging of body function, atherosclerosis, and other factors, patients undergoing carotid artery revascularization have a high degree of pre-operative frailty ( 38 , 39 ). Banning ( 40 ) found that the prevalence of pre-operative frailty of CEA is 23.9%, lower than the results of this study, which may be related to the inclusion of CAS patients and expanded sample size in this study.…”
Section: Discussioncontrasting
confidence: 73%
“… 25 , 26 Studies demonstrated that high GGT level was associated with the poor prognosis of patients with various tumours, including CCA. 27 , 28 Albumin is an important component in human plasma and a good indicator of liver dysfunction and malnutrition. The albumin level in the body obviously affected the survival time of cancer patient.…”
Section: Discussionmentioning
confidence: 99%
“…GGT as a ubiquitous epithelial enzyme was believed to be related to cardiovascular disease and chronic kidney disease 25,26 . Studies demonstrated that high GGT level was associated with the poor prognosis of patients with various tumours, including CCA 27,28 . Albumin is an important component in human plasma and a good indicator of liver dysfunction and malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Frailty syndrome is measured as the sum of various indicators, including unintentional weight loss, fatigue, muscle weakness, low physical activity, low gait speed, poor balance, visual impairment, and cognitive impairment [41,42]. The prevalence of preoperative frailty varies significantly (up to 50-60%) depending on age and the type of surgery, with a steep increase observed in older patients [43][44][45][46]. Preoperative frailty is known to be associated with poor postoperative morbidity and mortality [47].…”
Section: Preoperative Cognitive Assessmentmentioning
confidence: 99%